ASSESSMENT OF TREATMENT OUTCOMES FOR BREAST ABSCESSES IN POSTPARTUM WOMEN AT NAM DINH OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
This study aims to assess the effectiveness of breast abscess treatment for postpartum women at Nam Dinh Obstetrics and Gynecology Hospital.Subjects and methods: A longitudinal descriptive study was conducted on postpartum women who received treatment for breast abscess at Nam Dinh Obstetrics and Gynecology Hospital from January 1, 2025, to June 30, 2025.Results: 56 patients, primarily women, 1-4 months postpartum, accounted for 64.2% of cases and met the inclusion criteria. 87.1% of abscesses were unruptured, 94.6% had one abscess, and 75% had an ultrasonographic size of at least 5 cm. 87.5% of abscesses were cut radially, and packing was done after the treatment. 98.2% of cases had no signs of infection following drainage; the site healed properly, and the abscess entirely vanished. Following treatment, there were no instances of milk leakage. 94.6% of subjects had bilateral breastfeeding following therapy. 98.3% of patients were cured.Conclusion: The method of incision and drainage of breast abscesses has good treatment results, with most patients undergoing radial incisions, especially for abscesses ≥5 cm in size on ultrasound.
Keywords: Breastfeeding women, breast abscess, incision, drainage.